2014
DOI: 10.1155/2014/303929
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Tregs Is a Positive Prognostic Marker in Patients with HPV-Positive Oral and Oropharyngeal Squamous Cell Carcinomas

Abstract: Background. Human papillomaviruses (HPVs) have been proved as one of the etiological factors of oropharyngeal squamous cell carcinoma (OPSCC). Patients with tumors of viral etiology have a lower recurrence rate and better prognosis. OPSCC is linked to an alteration in the immune system. Only a limited number of studies have correlated both the immunological parameters and HPV status with patient prognosis. The aim of this study was to determine whether HPV infection and the immunological status influence patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 46 publications
6
60
1
Order By: Relevance
“…Of the included studies, seven articles investigated the relation between HPV status and circulating T cells, using flow cytometry. Four of these studies also studied the HPV-specific T-cell response and HPV status [1,5,6,11,14,18,19]. The relation between tumor infiltrating lymphocytes (TILs) and HPV status was the subject of research in 12 studies, using immunohistochemistry [2–4,7–10,15–17,20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included studies, seven articles investigated the relation between HPV status and circulating T cells, using flow cytometry. Four of these studies also studied the HPV-specific T-cell response and HPV status [1,5,6,11,14,18,19]. The relation between tumor infiltrating lymphocytes (TILs) and HPV status was the subject of research in 12 studies, using immunohistochemistry [2–4,7–10,15–17,20].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one of these articles described a significant decrease in naïve T cells and significant increase of effector T cells and effector memory T cells in HPV+, compared with HPV- OPSCC [18]. Two other articles showed that circulating CD4+ cells were decreased in HPV+ OPSCC, compared with HPV- OPSCC, although this was not significant [5–9,14,18,19]. In contrast, one article showed an increase of CD4+ cells, but again this was not significant [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated an increased population of CD8+ lymphocytes, Tregs and increased CD8+/Treg ratio in HPV+ OPC, which are associated with improved prognosis (31,32).…”
Section: Immune System and Cancer Developmentmentioning
confidence: 99%